Bailey Douglass: capstone - Douglass, Bailey, artist (Colorado State University. Libraries, 2022)
The artist's statement: Inner Dialogue, a collection of tableaux collages that speak to the different ways we mentally process situations and conflict. For me, there are four distinct parts that are in constant inner conflict that I wanted to expose. The four characters in this series are: 1. The Truest Form, my main consciousness. The actions of all the characters directly affect her. 2. A People Pleaser: She wears a red wig to emphasize her need for attention. 3. The Parent: I keep her in my own hair but dress her in blue, a color I associate with nurturing. The parent is complex, trying to keep me safe, making sure everything is as it should be. 4. Depression: I dress her in a black blunt wig with bangs to show her tendency to hide and to emphasize her lack of vibrancy. I play all four of these characters in all my pieces. I photograph them separately and then collage them together later in photoshop to create these narratives. Creating a physical manifestation of these conversations allows me to better understand how I respond to different scenarios. It also makes it easier to recognize when the conversations become toxic or problematic. It has given me the power to slowly change and reframe my thinking. Slowly transferring the power from my characters to the Truest Form. All people engage in Inner Dialogues. Knowing this, we can feel less alone.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: photography